Juridical Study of Problematic Overlapping Land Ownership Status in Indonesia - Pahrazi, Raihan; Farma Rahayu, Mella Ismelina (Journal of Law, Politic and Humanities, 2024)
Land rights, including cultivation rights, are an important aspect of a country's economic and social development. However, the complexity in implementing land rights is often a source of problems, especially related to overlapping land ownership and use status. Cultivation rights are a form of land right that has a primary nature. This means that this right gives permission to the holder to use the land in accordance with the specified purposes. The process of land registration and issuance of certificates by the National Land Agency (BPN) should provide clarity regarding ownership of land rights. However, in practice, there are still overlapping land ownership statuses which give rise to various problems. This problem involves land registration policies which are not yet fully capable of providing legal certainty for certificate holders. A land registration system that uses a negative approach, where land certificates are not an absolute means of proof, complicates the process of resolving land disputes. The impact is felt on people's lives, where land certificates become proof of ownership that has economic value. Concrete steps are needed to ensure clear land ownership and no overlap. This includes improving the land registration system, increasing coordination between relevant institutions, as well as outreach to the public about the importance of having a valid land certificate. The problem of overlapping land ownership is a serious challenge that needs to be addressed immediately. With cooperation between stakeholders and concrete steps, it is hoped that legal certainty in land ownership can be created, which will ultimately support sustainable development and community welfare.